TINGKAT KEPUASAN PEMUSTAKA DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA SOLOK: ANALISIS LIBQUAL+TM - Cherly pratiwi (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
This study discusses the level of user satisfaction of the Solok City Library and Archives Service which was analyzed using Libqual+Tm. Libqual+Tm. Consists of three dimensions, namely affect of service, information control and library as place. The purpose of this study is to describe the level of user satisfaction at the Solok City Library and Archives Service. This research is a quantitative research with descriptive method. Data collection techniques through interviews and questionnaires. The research data was obtained from distributing questionnaires to the users of the Solok City Library and Archives Service as a population. Sampling from the study using incidental sampling technique and obtained a sample of 50 people. Based on the results of the study, the following conclusions were drawn: (1) based on the dimensions of the officer's performance in serving (affect of service) the users felt quite satisfied with the Adequacy Gap (AG) the dimension was positive with a score of 0.05 and the level of user satisfaction with the library was considered very satisfied. with the Superiority Gap (SG) is positive with a score of 0.52; (2) based on the dimensions of information quality and access to information (information control) the users are not satisfied with the Adequacy Gap (AG), the dimension is negative with a score of -0.20 and the level of user satisfaction with the library is considered very satisfied with the Superiority Gap (SG) is positive with score 0.25; (3) based on the dimensions of library facilities and infrastructure (library as place) the users are quite satisfied with the Adequacy Gap (AG) with a value dimension of 0.013 and the level of user satisfaction with the library is considered very satisfied with the Superiority Gap (SG) with a positive value with a score of 0.50 . Overall, the level of user satisfaction, the level of satisfaction of the users of the Library and Archives Service of Solok City, the users are quite satisfied with the average Adequacy Gap (AG) is positive with a score of 0.08 and the level of user satisfaction with the library is considered very satisfied with the average Superiority (SG). positive value with a score of 0.4.